Defense Mechanisms in the Character of Atlas Shepherd in Atlas (2024): A Psychoanalytic Study - Hilmatul Ngafiah; Irma Rahmawati (PT. Alahyan Publisher Sukabumi, 2026)
The film Atlas (2024) presents anxiety about the development of artificial intelligence through the psychological conflict of its main character. This study discusses the issue of trauma and fear of Artificial Intelligence (AI) experienced by Atlas Shepherd due to a traumatic experience in the past. The main objective of this study is to identify the types of defense mechanisms used by Atlas Shepherd and also explain how these mechanisms help Atlas face trauma and fear of AI. This study uses a qualitative descriptive method with a psychoanalytic approach based on Anna Freud's theory. Data were obtained from dialogues, scenes, and actions of the main character in the film Atlas (2024) that show psychological conflicts and emotional responses. The results show that Atlas Shepherd uses four main defense mechanisms: denial, repression, projection, and rationalization. Denial is the most dominant mechanism, followed by other mechanisms, which function as psychological strategies to reduce anxiety and protect oneself from emotional distress. These findings confirm the relevance of psychoanalytic theory in understanding psychological conflicts in contemporary science fiction films.